ANALYSIS OF THE DIGLOSSIA OF THE SPEECH OF THE PEOPLE OF TASIKMALAYA DISTRICT IN RURAL TRANSPORTATION (AP) - Naila Riski Ahsani; Ulfah Fauziah; Ichsan Fauzi Rahman (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research is motivated by the finding of a change in the situation in the use of the language of the Tasikmalaya Regency community that occurs in the Rural Transport (AP). This study aims to determine the differences in language use based on the diglossia of Sociolinguistic studies as a result of analysis with qualitative descriptive methods. The data collection techniques are reading, listening, processing and data techniques. The research subjects are the people of Tasikmalaya Regency who use Rural Transportation (AP) with the object of research on diglossia of Sociolinguistic studies. The results of the research based on the analysis of the data obtained, namely the phenomenon of variation in the use of high language (T) and low language (R) in the interaction of Tasikmalaya Regency people using Rural Transport (AP) which is classified into several groups from drivers, teachers, students, students, factory employees, and buskers.